2011
DOI: 10.1007/s10646-011-0799-6
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal effects induced by a mixture of three non-steroidal anti-inflammatory drugs (NSAIDs) on the freshwater bivalve Dreissena polymorpha

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are the sixth top-selling drugs worldwide and are commonly found in freshwater ecosystems in the high ng/l to low μg/l range. Recent studies have investigated both the acute and the chronic toxicity of single NSAIDs on different biological models, but these studies have completely neglected the fact that, in the environment, non-target organisms are exposed to mixtures of drugs that have unforeseeable toxicological behavior. This work investigated the sub-lethal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 67 publications
0
33
1
Order By: Relevance
“…Similarly, increases in GPx activity have been described by Parolini et al (2010) after acutely exposing zebra mussel (Dreissena polymorpha) to acetaminophen, but also in other antioxidant enzymes (catalase, superoxide dismutase, and GSTs). The work described by Parolini and Binelli (2012) showed that GPx activity could also be enhanced after paracetamol exposure in the freshwater bivalve D. polymorpha. According to Aouacheri et al (2009), GPx enhancement caused by paracetamol is not restricted to aquatic biota; blood GPx activity of mammals was also responsive to acetaminophen oral administration.…”
Section: Acetaminophenmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, increases in GPx activity have been described by Parolini et al (2010) after acutely exposing zebra mussel (Dreissena polymorpha) to acetaminophen, but also in other antioxidant enzymes (catalase, superoxide dismutase, and GSTs). The work described by Parolini and Binelli (2012) showed that GPx activity could also be enhanced after paracetamol exposure in the freshwater bivalve D. polymorpha. According to Aouacheri et al (2009), GPx enhancement caused by paracetamol is not restricted to aquatic biota; blood GPx activity of mammals was also responsive to acetaminophen oral administration.…”
Section: Acetaminophenmentioning
confidence: 99%
“…The pathway of conjugation of paracetamol with glutathione vis GSTs activity was observed in mammals, where high drug levels are oxidized by enzymes of the CYP 450 mixed-function oxidase (MFO) system, forming NAPQI (Bowles et al, 2005), which promptly reacts with glutathione (Huber et al, 2009). In addition, Parolini and Binelli (2012) described the combined effects of paracetamol in a mixture with other non-steroidal anti-inflammatory drugs (such as diclofenac and ibuprofen) on the freshwater bivalve D. polymorpha; the obtained results evidenced a significant increase in GSTs activities after acute exposure to the mixture. The involvement of GSTs, in our case, did not seem to occur, reinforcing the lack of a strong oxidative-based response.…”
Section: Acetaminophenmentioning
confidence: 99%
See 1 more Smart Citation
“…However few studies addressed the effects of those contaminants on these organisms (e.g. Gagné et al, 2006a;Canesi et al, 2007;Parolini and Binelli, 2012), being necessary additional information to better understand the toxicity that drugs may pose to this group of marine invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large number of studies describing similar outcomes in many distinct organisms (please see references above), it is believed that this mechanism of paracetamol toxicity can be widely conserved and is likely to also occur in aquatic organisms. In fact, previous studies aiming to assess the effects of paracetamol in aquatic invertebrate species revealed the effects of this drug to bivalves (Corbicula fluminea, Brandão et al 2011;Ruditapes decussatus and Ruditapes philippinarum, Antunes et al 2013;Dreissena polymorpha, Parolini et al 2010;Parolini and Binelli 2012;Parolini et al 2013) and to crustaceans (Daphnia magna, Nunes et al 2014a). Additionally, similar effects were also reported for vertebrates, such as fish (Oncorhynchus mykiss, Ramos et al 2014; Anguilla anguilla, Nunes et al 2015), and for plants (Lemna gibba and Lemna minor, Nunes et al 2014b).…”
Section: Introductionmentioning
confidence: 99%